1998
DOI: 10.1161/01.str.29.6.1092
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficiency Tools Improve Stroke Management in a Rural Southern Health System

Abstract: Background and Purpose-Ischemic stroke is a high-volume and financially draining diagnosis at this rural health system.The purpose of this clinical practice analysis was to identify resource utilization and clinical process inefficiencies and to promote clinically efficient, evidence-based improvements. Methods-A retrospective analysis of medical record and financial databases of 356 patients with ischemic stroke was performed. The medical record data were adjusted for severity, and outliers were eliminated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…To account for differences in the relative prevalence of various stroke subtypes during time or hospital type comparisons, we used the previously described method 5 for adjustment. We used the 2 test for categorical data and analysis of variance for continuous data to detect any significant differences in variables among 3 types of facilities and between 1990 to 1991 and 2000 to 2001 and applied the Bonferroni adjustment when making multiple comparisons.…”
Section: Methodsmentioning
confidence: 99%
“…To account for differences in the relative prevalence of various stroke subtypes during time or hospital type comparisons, we used the previously described method 5 for adjustment. We used the 2 test for categorical data and analysis of variance for continuous data to detect any significant differences in variables among 3 types of facilities and between 1990 to 1991 and 2000 to 2001 and applied the Bonferroni adjustment when making multiple comparisons.…”
Section: Methodsmentioning
confidence: 99%
“…Questionnaire responses were tested for internal validity by comparing responses to similar questions. On the basis of these results and outcomes of previous studies, 2,6,[11][12][13][14][15][16][17] several specific institutional characteristics were chosen as treatment variables for further study. All institutional questionnaire responses demonstrating internal consistency and variability were tested for their effect on outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…2 Other studies have shown that more systematic stroke care improves efficiency, but few have evaluated mortality or functional outcomes. [3][4][5][6] The BAC recognized the importance of outcome-based research to establish the efficacy of stroke centers. 1 In an attempt to evaluate the elements of stroke centers recommended by the BAC, we examined their effects on ischemic stroke outcomes in a cohort of patients admitted to academic medical centers throughout the United States.…”
mentioning
confidence: 99%
“…36 -38 Such protocols can be implemented across a multihospital system to reflect individual diagnostic capabilities and treatment preferences. 31,39 For a PSC, such protocols should include the emergent care of patients with ischemic and hemorrhagic strokes, including stabilization of vital functions, initial diagnostic tests, and the use of various medications. These protocols could be based on previously published ones or could be developed by a multidisciplinary team organized by the Stroke Center.…”
Section: Written Care Protocolsmentioning
confidence: 99%